Drug susceptibility profiling and genetic determinants of drug resistance in Mycobacterium simiae isolates obtained from regional tuberculosis reference laboratories of Iran - Daneshfar, Sara; Khosravi, Azar Dokht; Hashemzadeh, Mohammad (PLOS ONE, 2022)
Background Among Non-tuberculous mycobacteria (NTM) which generally cause opportunistic infections, especially in immunocompromised hosts, Mycobacterium simiae (M. simiae) is one of the most important NTM, associated with pulmonary disease. The main concern about M. simiae infections is the extreme resistance of this NTM to antibiotics. There are limited studies about drug susceptibility testing (DST) and the causes of drug resistance in M. simiae. Hence, the current study aimed to identify the M. simiae isolates and to assess the drug resistance of the isolates using phenotypic and molecular methods. Materials and methods In this study, 50 clinical pulmonary isolates suspected of NTM were collected from regional tuberculosis reference laboratories in Iran. The isolates were identified as M. simiae by using standard biochemical tests and molecular methods. DST was performed for identified M. simiae isolates and additional 35 M. simiae isolates from the department archive, against eight drugs. The mutations in gyrA, gyrB, and rrl genes in clarithromycin and moxifloxacin resistant isolates were investigated by polymerase chain reaction (PCR) followed by sequencing. Results Out of 50 suspected NTM isolates, 25 isolates were detected as M. simiae species based on the biochemical tests, and 18 isolates were verified based on the rpoB gene sequence analysis to achieve a total of 53 isolates when the archive isolates were included. DST results showed that all 53 isolates were resistant to isoniazid, rifampin, and clofazimine. The rate of resistance to ethambutol and linezolid were 34 (64%), and 40 (76%) respectively. The highest susceptibility rate was demonstrated for amikacin 53 (100%) and clarithromycin 45(85%), followed by moxifloxacin 35(66%). Sequence analysis showed mutations in positions 2058 and 2059 of the rrl gene, as well non-synonymous mutation at codons 389, 444, and 571 of the gyrB gene. Sequence analysis showed no mutation in the gyrA gene. drug-resistant isolates with mutations showed higher MICs compared to non-mutant resistant isolates. Conclusions This study revealed amikacin, clarithromycin, and moxifloxacin as the most effective antibiotics. However, since M. simiae exhibited a high level of antibiotic resistance in vitro, therefore, species identification and determining the antibiotic susceptibility pattern of the isolates are essential before treatment.